Role of MDCTA in Bronchial Artery Embolization in patients with Hemoptysis - Panday, Shailesh Kumar; Mandal, Sandip Kumar; Gnawali, Suman; Sharma, Nitu; Adhikari, Ganga Dutta; Yadav, Ajay Kumar (Nepalese Journal of Cancer, 2023)
Objective:To evaluate the role of bronchial artery MDCTA in bronchial artery embolization in the treatment of haemoptysis patients.Methods: 46 patients treated with bronchial artery embolization for haemoptysis was included in the study at 1st Affiliated Hospital, Jinzhou Medical University. They were classified into 2 groups, Group A-Preoperative CTA and Group B -Simple DSA. Group A (n=28) is those with preoperative CTA examination performed, while group B (n=18) is those who performed DSA directly without preoperative CTA. The results of CTA and DSA, technical and clinical outcome compared and analyzed.Results: 48 bleeding arteries were identified in group A while 24 bleeding arteries were identified in group B. These arteries were embolized successfully. In the group A total fluoroscopy time, total operative time, and contrast dose were shorter than group B respectively (8.42± 2.82; 28.34± 5.61; 27.86± 6.42 VS. 18.46± 10.34; 40.27±16.32; 62.59±19.48).Conclusion: Bronchial artery CTA can objectively evaluate haemoptysis associated with vascular origin, number and its shape and it can reduce the operative time and reduce the radiation exposure to doctors and patients too, it increase the success rate of haemoptysis interventional therapy guidance has wide clinical application value